2018
DOI: 10.1088/1757-899x/292/1/012084
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sound absorbing performances of copper foam and iron foam with the same parameters

Abstract: Abstract. Sound absorbing performances of the copper foam and the iron foam with the same parameters were investigated by the AWA6128A detector according to standing wave method. Two modes were investigated, which included the pure metal foam mode and the combination mode with the settled thickness of metal foam. In order to legibly compare the sound absorbing coefficients of the two metal foams, the detected sound frequency points were divided into the low frequency range (100 Hz ~ 1000 Hz), the middle freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…It could be found that the theoretical expression of the sound absorbing coefficient was extraordinary complicated, which limited its application in predicting sound absorbing coefficient [12]. What's more, establishments of these parameters in Eq.…”
Section:  mentioning
confidence: 99%
“…It could be found that the theoretical expression of the sound absorbing coefficient was extraordinary complicated, which limited its application in predicting sound absorbing coefficient [12]. What's more, establishments of these parameters in Eq.…”
Section:  mentioning
confidence: 99%